Identification of SGS 1609 Cellulolytic Bacteria Isolated from Sargassum spec. and Characterization of The Cellulase Produced - Yusro Nuri Fawzya; Stenny Putri; Nita Noriko; Gintung Patantis (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2013)
Bacterial isolate from seaweed designated as SGS 1609 was previously found to be able to produce cellulase represented by formation of clear zone on solid medium containing carboxymethylcellulose (CMC). This research was conducted to identify the isolate and determine optimum production time as well as characterize the cellulase produced. The isolate was identified using 16s-rRNA gene analysis. Cellulase production was conducted by cultivating the isolate in the liquid medium containing CMC followed by centrifuging to get supernatant as the crude enzyme. The enzyme was then concentrated using ammonium sulfate precipitation and ultra filtration. The concentrated enzyme having higher activity produced from the concentration process was then characterized to determine its optimum pH and temperature, heat stabilization, metal ions effect and substrate specificity. The result showed that the SGS 1609 isolate was identified as Serratia marcescens with 99% similarity. The isolate produced cellulase optimally at 4 days incubation. Ultra filtration produced higher enzyme activity compared to NH4-sulfate precipitation. The enzyme concentrated by ultra filtration worked optimally at the pH of 7, temperature of 50 oC, stable at the temperature of 60 oC for 240 minutes and was increased its activity by Ca2+ and Mg2+ ions. On the other hand, the enzyme was inhibited by Fe3+, Zn2+ and Na+ ions, but was not relatively affected by K+ and EDTA. The use of conventional agar producer waste treated with 6% NaOH gave highest activity compared to other substrates.